Дневник фокса Микки - Черный Саша (Читаем всей семьей, 2016)
Экземпляры: СБ (20170320) / Инвентарный номер: 53681 / Цена: 311.00 / Сис.шифр: Р2мл / Авт.знак: Ч-49 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6